Determination of places of contest participants in general case - Stakvilevičius , M.; Dargis , F. (Psichologija, 1971)
The system of linear equations, presented in the Collection No 10, is generalised in the present article as representing the case of contests when separate single combats are estimated using any system of marks. Besides, a way is indicated for distributing places of contest participants by numerical methods with the help of the simple iteration process.